Cis-isomerism and other chemical requirements of steroidal agonists and partial agonists acting at TRPM3 channels - Majeed, Y (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: The transient receptor potential melastatin-3 (TRPM3) channel forms calcium-permeable, non-selective, cationic channels that are stimulated by pregnenolone sulphate (PregS). Here, we aimed to define chemical requirements of this acute steroid action and potentially reveal novel stimulators with physiological relevance. EXPERIMENTAL APPROACH: We used TRPM3 channels over-expressed in HEK 293 cells, with intracellular calcium measurement and whole-cell patch-clamp recording techniques. KEY RESULTS: The stimulation of TRPM3 channels was confined to PregS and closely related steroids and not mimicked by other major classes of steroids, including progesterone. Relatively potent stimulation of TRPM3-dependent calcium entry was observed. A sulphate group positioned at ring A was important for strong stimulation but more striking was the requirement for a cis (β) configuration of the side group, revealing previously unrecognized stereo-selectivity and supporting existence of a specific binding site. A cis-oriented side group on ring A was not the only feature necessary for high activity because loss of the double bond in ring B reduced potency and loss of the acetyl group at ring D reduced efficacy and potency. Weak steroid stimulators of TRPM3 channels inhibited effects of PregS, suggesting partial agonism. In silico screening of chemical libraries for non-steroid modulators of TRPM3 channels revealed the importance of the steroid backbone for stimulatory effects. CONCLUSIONS AND IMPLICATIONS: Our data defined some of the chemical requirements for acute stimulation of TRPM3 channels by steroids, supporting the existence of a specific and unique steroid binding site. Epipregnanolone sulphate was identified as a novel TRPM3 channel stimulator.